BIMBINGAN KELOMPOK MODEL PERMAINAN UNTUK MENINGKATKAN KREATIFITAS ANAK - Dinar Mahdalena Leksana (JCE (Journal of Childhood Education), 2018)
The goal of this research was to test the effectiveness of using group guidance service with learn to behave game to increase the children’s creativity. This research was conducted by pre-test post-test one group design. The subject of this research were 14 children’s TK A Ma’arif Payaman. Data analysis technique used in this research was Wilcoxon’s signed rank test. It was found that there was a significant difference between the ability of self adjustment at school score before and after treatment. Based on the Wilcoxon test it was found that T count = 0, N = 14 with 0,01 significant level so T table = 0,05. It means T count < T table (0<0,05). So hypothesis of this research was accepted. It can be concluded that group guidance service with learn to behave game was an effective approach to to increase the children’s activity